The Experience among Patients with Bone Fractures during Traditional Massage Therapy (Topu Bara): A Phenomenology Study - La Rakhmat Wabula; Endah Fitriasari; Syahfitrah Umamity; Arindiah Windari (Palembang MediRose Publisher, 2022)
Background: In Indonesia, traditional medicine called â€œSangkal Putungâ€ has become an alternative treatment for fractures. Broken-bones sufferers at any age, anywhere, and in any case go to â€œSangkal Putungâ€ and there is even a public hospital that provides surgical services. Especially in Maluku Province, there is a type of traditional massage therapy treatment called â€œTopu Baraâ€. Purpose: The study aimed to explore the experiences among patients with bone fractures during traditional massage therapy (Topu Bara). Methods: A phenomenological study that used deep interviews was used from August to September 2021 The participant was taken by purposive sampling, adult aged 25 to 55-years old, and were the second or more of healing series. Data originated from 15 participants. Interviews were recorded, transcribed verbatim, and Collaizi analysis. Results: The results of the study found 7 themes, including causes of fracture, time events, action taken directly after inside, pain experiences during handling in therapy â€œTopu Baraâ€, coping of the patients, pain management, and advice given by healer to other participants. Conclusions: Most of them stated that safety and comfort were the priority for fracture healing. The concept of culture in the behavioral alteration of fracture healing can have on the participants.